Short term effects of heavy metals on enriched anammox culture - Uzunhasanoğlu, Ayşe Ekin (My University, 2017)
Çevre mühendisliği açısından, anammox prosesi, yenilikçi bir azot giderim teknolojisidirancak, bu yenilikçi teknolojiyi arıtımda kullanabilmek için, atıksu karakterinin anammoxbakterisiyle olan uyumu incelenmelidir.

For the point of environmental engineering anammox is a novel nitrogen removal technologyand in order to be able to use this innovative technology, compatibality between wastewaterand anammox bacteria should be investigated.
Keywords: ağır metal; Anammox; Anommox sistemi; Arıtma; Arıtma sistemleri; Atık sular; azot giderimi; Azot giderme; Çevre, Mühendislik; heavy metals; molecular tools; moleküler teknikler Anammox; nitrogen removal; Su; Teknoloji